Circles of culture: literacy as a pro- cess for social inclusion - Souto Manning, Mariana (Colombian Applied Linguistics Journal, 2004)
Historically, illiteracy has been a reality for Brazilians. This paper describes an adult literacy program currently in practice in Northeastern Brazil from a critical theory framework. The program described is based on Freireʼs circles of culture and its conception is that literacy is a process for social inclusion. Along with the description provided by the author, resulting from participant observation and review of literature, this paper includes the perspective of a student currently in the program. Further, from a critical standpoint, the author acknowledges many positive things already implemented and challenges for the future of this promising literacy program.